Correction: Xia et al. A Quantum-Resistant Identity Authentication and Key Agreement Scheme for UAV Networks Based on Kyber Algorithm. Drones 2024, 8, 359 - Tao Xia; Menglin Wang; Jun He; Gang Yang; Linna Fan; Guoheng Wei (Drones)
There was an error in the authorship of the original publication [...]